Asas Kebebasan Berkontrak Perjanjian Sewa Menyewa Tanah (Analisis Putusan Mahkamah Agung Nomor 3693 K/Pdt/2020). - Walangitan, Semuel; Taqiyah, Lutfiatut (Neolectura, 2024)
Land is a very basic need for human life. Humans live and carry out activities on land, so it can be said that almost all human life activities, both directly and indirectly, always require land. In this case, the application of the principle of contract can also be linked to the discussion of the author's thesis, namely the principle of freedom of contract, which can be reviewed in Article 1321 of the Civil Code, as the content of this legal rule is: